Moxibustion as adjuvant therapy for preventing bone loss in postmenopausal women: protocol for a randomised controlled trial - Xin Zhang; Ning Li; Lu Liu; Leixiao Zhang; Lingyun Lu; Qian Wen; Jianqin Lv; Xijie Yu (BMJ Open)
Introduction Postmenopausal osteoporosis, caused by ageing and oestrogen deficiency, seriously threatens women’s physical and mental health. Postmenopausal osteopenia is the transition from healthy bone to osteoporosis, and it may be the key period for preventing bone loss. Moxibustion, a physical therapy of Traditional Chinese Medicine, has potential benefits for osteoporosis treatment and prevention, but it has not been adequately studied. This study aims to explore the clinical effects and safety of moxibustion in delaying bone loss in postmenopausal women.Methods and analysis In this parallel-design, randomised, patient-blind and assessor-blind, controlled clinical study, 150 women with osteopenia at low fracture risk will be randomly assigned to a moxibustion treatment (MT) group or a placebo-moxibustion control (PMC) group in a 1:1 ratio. In addition to the fundamental measures (vitamin D3 and calcium) as recommended by the guidelines, participants of the two groups will receive MT or PMC treatment for 42 sessions over 12 months. The primary outcome will be the bone mineral density (BMD) of the lumbar spine at the end of the 12-month treatment, and secondary outcomes will be the BMD of the femoral neck and total hip, T-scores, bone turnover markers, serum calcium levels, serum magnesium levels, serum phosphorus levels, serum parathyroid hormone levels and 25-hydroxyvitamin D levels, intensity of bone pain, quality of life, incidence of osteoporosis and fractures, usage of emergency drugs or surgery, participant self-evaluation of therapeutic effects and the rate of adverse events. All statistical analyses will be performed based on the intention-to-treat and per-protocol principle.Ethics and dissemination Ethics approval has been obtained from the Ethics Committee on Biomedical Research, West China Hospital of Sichuan University (permission number: 2021-1243). The results are expected to be published in peer-reviewed journals.Trial registration number ChiCTR2100053953.